MORPHOMETRIC ANALYSIS OF INDIAN MACKEREL (Rastrelliger kanagurta) LANDED IN KUPANG IN OCTOBER AND NOVEMBER: LENGTH RATIO AND LINEAR RELATIONSHIP OF TL-FL-SL - Larwuy, Winster; Hidayati, Desy A.; Palinggi, Rifka L.; Armos, Nikanor H.; Boikh, Lebrina Ivantry; Ayubi, Aludin Al; Maitindom, Frits A. (Universitas Nusa Cendana, 2025)
Abstract - This study was conducted to analyze the morphometric characteristics of Indian mackerel (Rastrelliger kanagurta) landed in Kupang during October – November 2025. Morphometric analysis was performed as body-length parameters constitute fundamental biological indicators for assessing growth patterns, detecting variations in body form, and generating essential size-conversion metrics that support population biology and stock-management assessments. A total of 303 individuals were measured for Total Length (TL), Fork Length (FL), and Standard Length (SL) to analyze size distribution, analyze length ratios (FL/TL, SL/TL, SL/FL), and analyze linear relationships between parameters using linear regression and two-way ANOVA to test the effects of size class and ratio type. The size distribution indicated that TL ranged from 21.0 to 32.1 cm (mean = 25.708 ± 3.601 cm), with FL ranging from 19.0 to 29.1 cm and SL ranging from 17.7 to 26.5 cm. Length ratios were relatively stable in small to medium size but decreased in larger individuals, suggesting disproportionate length growth. The ANOVA results revealed significant effects of size class and ratio type on body-length ratios (p < 0.05). Linear relationships between the length parameters exhibited a negative allometric growth pattern (b < 1), accompanied by extremely high correlation coefficients (r = 0.998 for TL-FL, TL-SL, and FL-SL), indicating that FL and SL increased proportionally more slowly than TL. Keywords: indian mackerel, morphometry, length ratio, negative allometry, Kupang